Pogled Katoliške Cerkve na razvoj in uporabo umetne inteligence - Globokar, Roman (Bogoslovni vestnik, 2024)
Christian ethics, with its anthropological and theological presuppositions, enters into the wider debate on the ethical dilemmas of artificial intelligence. This article presents the content of three official documents of the Catholic Church on artificial intelligence, namely the 2020 “Roman Call for an Ethics of Artificial Intelligence” and the two 2024 Messages of Pope Francis. It illuminates the content of the documents through three criteria that define the specific relevance of the Christian faith for ethics: integration, stimulation, and critical judgement. The article notes that the texts are addressed to all people, not just the Catholics and that they integrate the most up-to-date insights and ethical debates on the development and use of artificial intelligence. Based on biblical anthropology, they stimulate development that will ensure respect for the dignity of every human person, the equality of all people in society, greater global justice and interconnectedness of humanity, and respect for the natural environment. As a specific criterion of ethicality, the documents cite attention to the poor and the more vulnerable members of society. Faith in a creator God prevents the absolutization of the acquisitions of the human mind and empowers a critical assessment of artificial intelligence. The article, in harmony with the documents of the Catholic Church, encourages the development of ethical guidelines for the development and use of artificial intelligence. However, the author of the article is convinced that rules alone will not be enough, and therefore also stresses the need to strive for the development of fundamental ethical attitudes, especially in the field of education and training. Based on the content of the Church's social teaching, he presents eight virtues to ethically guide the further development of AI.
Keywords: artificial intelligence; critical judgement; dignity of the human person; dostojanstvo človeške osebe; Frančišek; kreposti; kritično presojanje; pope Francis; sustainable development; trajnostni razvoj; umetna inteligenca; universal brotherhood; vesoljno bratstvo; virtues